The MdXTHB gene is involved in fruit softening in 'Golden Del. Reinders' (Malus pumila). (14th August 2020) - Ma, Mengmeng; Yuan, Yongbing; Cheng, Chenxia; Zhang, Yong; Yang, Shaolan
Abstract: BACKGROUND: Fruit softening is a major determinant of commercial value and shelf life. A transcriptomic analysis of 'Golden Delicious' and 'Golden Del. Reinders' (a bud mutation of 'Golden Delicious' that readily softens) apple fruit was conducted during storage. RESULTS: A comparative analysis of the obtained expression profiles of fruit between two cultivars identified 1345 upregulated and 3475 downregulated differentially expressed genes (DEGs). The DEGs identified were associated with cellular processes and carbohydrate metabolism and were especially enriched in cell‐wall‐related genes. Among the cell‐wall‐related genes, the xyloglucan endotransglucosylase/hydrolases ( XTH ) gene MdXTHB was significantly upregulated and exhibited high expression levels in 'Golden Del. Reinders' fruit, which had a lower level of firmness relative to 'Golden Delicious'. Overexpression of MdXTHB in both 'Golden Delicious' and 'Fuji', which typically maintain high levels of firmness in storage, exhibited faster rates of softening and an earlier peak of ethylene production than empty‐vector‐infiltrated fruit did. CONCLUSION: The results of this study indicate that MdXTHB potentially promotes apple fruit softening by degrading the fruit cell wall. This result is also useful to designing further experiments on the molecular regulation of fruit softening in apple. © 2020 Society of Chemical Industry